Study of Residential Development in Urban Fairies - Priyono, Eko Agus; Tutuko, Pindo (International Conferences SDGs 2030 Challenges and Solutions, 2030)
The suburban area (pheri-urban) is a transition from the urban and rural areas that have different characteristics and attributes. This area is naturally formed due to developments and congestion that occur from the core city. One of the developmental factors is the interaction between the core cities and the peri peri urban areas. The greater the interaction that occurs the greater the development that occurs in the pheri pheri urban area. Interaction between urban and rural areas will naturally be bridged by the presence of urban pheri-urban areas. Population growth in the city center resulted in an increase in settlement requirements (serlin 2012) and that in the center of the city the developers have been unable to provide the need for settlement due to the high price of land in the city center and the limited land in the centers (Septanaya, 2012). This prompted the development of housing and settlement needs around the hinterland of the city center. With this sprinkling it will generate a snowballs effect, where with the existence of housing and settlement activities will arise ativitas and other needs such as social facilities needs, economic facilities needs, educational facilities, health facilities, office facilities etc. But in some locations there are also several factors that influence the growth of the pheri pheri, not only caused by the settlement of settlement needs from the city center but due to other factors, such as in Malang, the development of suburbs in Kedungkandang and Lowokwaru influenced by the existence of industrial activity. While the growth of suburbs in Banda Aceh (Ulee Kareng sub-district) is caused by the construction of new transportation line (Prof. Ali Hasyimi Street) thus the facilities and infrastructures or connectivity also influence the development of the periphery. In addition to the above matters more due to the activity that grows by itself there are important factors associated with the development of the periphery of government policy through Spatial Planning, where in each RTRW will be planned areas for residential areas for expansion of urban areas, in the area plan Strategic and spatial pattern will be directed towards the development of the city over the next 25 years, so that with the spatial is expected the development of the city will be directed, and easily controlled.